Primary ciliary dyskinesia: a rare case of CCNO mutation - Rajanna, Charitha; Karumbaiah Kalengada , Prarthana (International Journal of Contemporary Pediatrics, 2023)
Primary ciliary dyskinesia (PCD) is a heterogenous inherited disorder characterized by impaired ciliary function. Clinical manifestations include respiratory distress in newborn, bronchiectasis, repeated lower respiratory tract infections, rhinosinusitis, otitis media, left- right laterality defects and infertility. Estimated frequency of PCD is 1 in 12,000-20,000 live births, prevalence in children with repeated respiratory infections is 5%. The diagnosis is often delayed even if characteristic findings are present as the tests available for diagnosis is limited. 14-year-old adolescent female, second born child to a consanguineously married couple with history of repeated respiratory tract infections, diagnosed outside as uncontrolled bronchial asthma, with history of nasal polyps, presented with delayed puberty and short stature. On examination child was noted to have proportionate short stature with SMR of Tanner stage 1, with normal systemic examination. High-resolution computed tomography (HRCT) done was suggestive of mild bronchiectasis. Child was evaluated for short stature. In order to rule out diseases associated with ciliary dysfunction; clinical exome sequencing was sent which showed Primary ciliary dyskinesia secondary to homozygous mutation of CCNO gene which was autosomal recessive. Primary ciliary dyskinesia with CCNO is a rare presentation which can have situs solitus. It was first reported in 2014. In children presenting with bronchiectasis and delayed puberty one should think of suspect ciliary dysfunction. In the absence of situs inversus, one can still suspect PCD secondary to various other mutations.